Corticotropin-Releasing Factor Receptors in the Locus Coeruleus Modulate the Enhancement of Active Coping Behaviors Induced by Chronic Predator Odor Inoculation in Mice - Wang, Qiong; Liu, Yingjuan; Zhang, Jianxu; Wang, Weiwen (Frontiers in Psychology, 2020)
Stress inoculation experience has been proved to induce active coping behaviors to subsequent stress. However, the specific neural mechanisms underlying this effect remain unclear. In this study, a chronic and mild predator odor exposure model was established to investigate the effect of predator odor stress inoculation on behaviors in novel predator odor exposure, open field test and forced swimming test (FST), and on the expression of CRF receptors in locus coeruleus (LC) and dorsal raphe nuclei (DRN). The results showed that predator odor stress inoculation increased the active coping of mice under the severe stress environment without changing the stress response to a new predator odor. Meanwhile, in LC, the CRFR1 expression was increased by predator odor stress inoculation. These results suggested that predator odor stress inoculation can be used as an effective training method to improve active response to later severe stress and the function of CRFR1 in LC might be a potential underlying biological mechanism.